2016
DOI: 10.1111/jth.13181
|View full text |Cite|
|
Sign up to set email alerts
|

Tissue factor–positive tumor microvesicles activate platelets and enhance thrombosis in mice

Abstract: Background Cancer patients have an approximately four-fold increased risk of venous thromboembolism (VTE) compared with the general population, and cancer patients with VTE have reduced survival. Tumor cells constitutively release small membrane vesicles called microvesicles (MVs) that may contribute to thrombosis in cancer patients. Clinical studies have shown that levels of circulating tumor-derived, tissue factor-positive (TF+) MVs in pancreatic cancer patients are associated with VTE. Objectives We teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
145
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(152 citation statements)
references
References 72 publications
4
145
1
2
Order By: Relevance
“…Interestingly, colorectal cancer cell lines with mutations in both K- ras and p53 , such as the HCT116 subline 379.2, express higher levels of tissue factor (TF) than those with mutations in only K- ras , such as HCT116 [11]. There is also a wide range of TF expression in the different human pancreatic cell lines; HPAF-II, HPAC and BxPc-3 express high levels of TF, L3.6pl express medium levels, PANC-1 expresses low levels and MIAPaCa-2 do not express TF [1214]. The A549 epithelial-like lung cancer cell line was isolated from human cancerous lung tissue [15, 16].…”
Section: Choice Of Mouse Strain and Cancer Cellmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, colorectal cancer cell lines with mutations in both K- ras and p53 , such as the HCT116 subline 379.2, express higher levels of tissue factor (TF) than those with mutations in only K- ras , such as HCT116 [11]. There is also a wide range of TF expression in the different human pancreatic cell lines; HPAF-II, HPAC and BxPc-3 express high levels of TF, L3.6pl express medium levels, PANC-1 expresses low levels and MIAPaCa-2 do not express TF [1214]. The A549 epithelial-like lung cancer cell line was isolated from human cancerous lung tissue [15, 16].…”
Section: Choice Of Mouse Strain and Cancer Cellmentioning
confidence: 99%
“…The most popular are those involving the infrarenal vena cava (IVC). An advantage of the IVC is that high frequency ultrasonography can be used for non-invasive longitudinal monitoring of thrombus formation [14, 27, 28]. Clot formation is typically analyzed between 0–48 hours.…”
Section: Thrombosis Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, venous thrombosis is attenuated in mice rendered thrombocytopenic, 8 in those deficient in von Willebrand factor, 9 or in those treated with antiplatelet agents. 10 With venous flow restriction, endothelial cells become activated and attract platelets and neutrophils to form heterotypic aggregates. Activated neutrophils release neutrophil extracellular traps (NETs), lattices composed of DNA and histones, to which additional platelets adhere ( Figure 1).…”
Section: Pathogenesis Of Thrombosis Role Of Platelets In Arterial Andmentioning
confidence: 99%
“…As EVs typically contain similar membrane‐bound proteins as their mother cell, EVs can possess procoagulant activity that may contribute to VTE. Preclinical mouse models have demonstrated that TF + EVs are being shed from pancreatic cancer cells into the bloodstream, mediating platelet activation and thrombus formation 26, 27, 28. Unfortunately, a relationship between circulating TF + EVs and VTE in a clinical setting was only established in pancreatic cancer patients, while no correlation was found in other moderate‐to‐high‐risk groups such as brain, colorectal, or lung cancer patients 29, 30.…”
Section: Tissue Factormentioning
confidence: 99%